2023
DOI: 10.3390/ijerph20021454
|View full text |Cite
|
Sign up to set email alerts
|

Activity Restriction and Hospitalization in Pregnancy: Can Bed-Rest Exercise Prevent Deconditioning? A Narrative Review

Abstract: Evidence suggests that exercise during pregnancy is beneficial to both parent and fetus. However, there are high-risk pregnancy conditions that may warrant hospitalization. In our narrative review, we first describe the clinical implications for activity restriction in pregnancy, the effects of hospitalization, and the impact of bed rest on non-pregnant individuals. We provide examples of a 30 min bed-rest exercise program for hospitalized pregnant patients using the principal of suggested frequency, intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Movement restriction and bed rest, which are traditionally believed to be therapeutic during pregnancy, have been a common treatment option in premature rupture of membranes, vaginal bleeding, placenta previa, and multiple pregnancies (da Silva Lopes et al, 2017). However, studies have reported that mandatory bed rest does not prevent adverse perinatal outcomes (Hassan et al, 2022; Palacio & Mottola, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Movement restriction and bed rest, which are traditionally believed to be therapeutic during pregnancy, have been a common treatment option in premature rupture of membranes, vaginal bleeding, placenta previa, and multiple pregnancies (da Silva Lopes et al, 2017). However, studies have reported that mandatory bed rest does not prevent adverse perinatal outcomes (Hassan et al, 2022; Palacio & Mottola, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, physical activity restriction is a common strategy for preventing heart attacks in patients with severe cardiomyopathy [1,2]. Daily activity restriction in the upright position is recommended to prevent preterm births in high-risk pregnancies [3]. Excessive fear of falling can induce general daily activity restriction and is therefore regarded as a strategy for preventing falls in the older population [4].…”
Section: Main Textmentioning
confidence: 99%
“…Nevertheless, we realized through literature review that the measures of activity restriction still need to be standardized. In general, two methods have been used to assess activity restrictions in previous studies [1][2][3][4]: a qualitative approach based on self-perception and a quantification method based on the actual activity amount. The qualitative approach is used more commonly than the quantification method.…”
Section: Main Textmentioning
confidence: 99%
“…Nevertheless, there exists a significant knowledge gap on this topic within the realm of scientific literature. There is an urgent need to investigate the potential impact of alternative therapies, such as light physical activity, as a means to potentially alleviate the notable complications associated with bed rest during pregnancy [30].…”
Section: Introductionmentioning
confidence: 99%